Epidemiology of the STD Profiles patients assisted in national training center - Tibúrcio, Alberto S.; Passos, Mauro Romero Leal; Pinheiro, Vandira M.S. (Brazilian Journal of Sexually Transmitted Diseases, 2000)
This is a transversal study on 1182 out patients whosc medical rccords were opened at the Sexually Transmitted Diseases (STD) Sector, Universidade Federal Fluminense. Niterói. RJ, Brazil between January and December 1995. ln 698 out of these 1182 patients (59,0%). one or more infcctious diseases with presumable sexual transmission were diagnosed. A epidemiological study was done on this popularion, aiming to idcntify the rnost frequent causes for seeking medical advice at the STD Sector; to idcntify the STD/genital infcctious most frequent in these patients; to inspect (he distribution of socio-economic and educational variables among paticnts wilh and without STD/genital infections. 10 identify some behavioral factors that may have been implied in the acquisirion of these infections: to know 1he frequency of routine using of condoms; 10 assess the fax of subsequenl retum 10 the ST Sector: and 10 verify how many pa1ien1s were sexual contacts of others already undcr medical assistance. Thc author emphasizes the imponance of prelirninary descriptive cpidcmiologic: studies in the research of factors 1ha1 may interfere in lhe dynamics of these infections in a givcn population.